UPAYA KEGIATAN MUHAFADHOH DALAM MENINGKATKAN HAFALAN NADZOM IMRITI PADA MURID KELAS 4 MI MIFTAHUL HUDA - Amir Mukminin; Zamzam Mustofa; Nurin Fauziatul Akmala (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
This study aims to find out 1) how the muhafadhoh activities are carried out and 2) how much muhafadhoh activities are in improving the memorization of nadzom imriti in 4th grade students of MI Miftahul Huda. This research uses qualitative research with the type of case study research. This research was conducted directly in the field, observing directly and seeking information from direct informants. The data in this study were taken from observations, interviews, and documentation. The data analysis of this research went through the inductive analysis stage, which started its analysis from emotional facts not from theory. The results of this study are seen from the results of observations and interviews with several students, this muhafadhoh activity can really help improve the memorization of nadzom imriti in 4th grade students of MI Miftahul Huda. This result can be seen from the confessions of the interviewed students, they really felt the positive impact of the muhafadhoh activity. So they can memorize more easily than usual. This activity is also really helpful in passing the memorization test that they must pass at the end of each school year.